Two-soliton solutions of the Kadomtsevpetviashvili equation - Tiong, Wei King; Ong, Chee Tiong; Isa, Mukheta (Penerbit UTM Press, 2006)
Several findings on soliton solutions generated by the Kadomtsev-Petviashvili (KP) equation were discussed in this paper. This equation is a two dimensional of the Korteweg-de Vries (KdV) equation. Traditional group-theoretical approach can generate analytic solution of solitons because KP equation has infinitely many conservation laws. By using Hirota Bilinear method, we show via computer simulation how two solitons solution of KP equation produces triad, quadruplet and a non-resonance structures in soliton interactions